Access to Modern Energy: a Review of Barriers, Drivers and Impacts - Jacopo Bonan; Stefano Pareglio; Massimo Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2016)
Universal access to modern energy services, in terms of access to electricity and to modern cooking facilities, has been recognized as a fundamental challenge for development. Despite strong praise for action and the deployment of large-scale electrification programs and improved cookstove (ICS) distribution campaigns, few studies have shed light on the barriers to, the enablers of and the impacts of access to energy on development outcomes, using rigorous methodologies. This paper reviews this recent strand of research, trying to fill these gaps. We focus on the demand-side and household perspective. Our main outcomes of interest are electricity connection and ICS adoption for the analysis of barriers, time allocation, labour market outcomes and welfare for the impact analysis. We provide evidence of significant wellbeing impacts of electrification, and mixed evidence for cookstoves.
Keywords: O1; O13; Q4; Q48; 330; Impact Evaluation; Energy Poverty; Energy Access; Rural Electrification; Modern Cookstoves; Literature Review